A novel potent autophagy inhibitor ECDD-S27 targets vacuolar ATPase and inhibits cancer cell survival - Paha, Jiraporn (Sci Rep, 2019)
Autophagy is a conserved lysosomal-dependent cellular degradation process and its dysregulation has been linked to numerous diseases including neurodegeneration, infectious diseases, and cancer. Modulation of autophagy is therefore considered as an attractive target for disease intervention. We carried out a high-content image analysis screen of natural product-derived compounds to discover novel autophagy modulating molecules. Our screen identified ECDD-S27 as the most effective compound for increasing the number of autophagic vacuoles inside cells. The structure of ECDD-S27 revealed that it is a derivative of cleistanthin A, a natural arylnaphthalene lignan glycoside found in plants. ECDD-S27 increases the number of autophagic vacuoles by inhibiting the autophagic flux and is able to restrict the survival of different cancer cells at low nanomolar concentrations. Molecular docking and SERS analysis showed that ECDD-S27 may potentially target the V-ATPase. Upon treatment of various cancer cells with ECDD-S27, the V-ATPase activity is potently inhibited thereby resulting in the loss of lysosomal acidification. Taken together, these data indicated that ECDD-S27 retards the autophagy pathway by targeting the V-ATPase and inhibits cancer cell survival. The observed antitumor activity without cytotoxicity to normal cells suggests the therapeutic potential warranting further studies on lead optimization of the compound for cancer treatment.